Análise do desempenho de meios filtrantes na filtração de nanopartículas durante o aumento de sua queda de pressão - Lima, Bruno de Araújo (2019)
The performance of filter media in filtration is the main factor in choosing a material that meets the requirements for a filtration process. It takes into consideration the collection efficiency, permeability, pressure drop among other factors. The main objective of this work was the performance analysis of some filter media in the filtration of nanoparticles during the pressure drop increasing through loading with powder. This theme was chosen because the performance of the filter media throughout its use, from when new until its maximum pressure drop, is very important for determining the useful life and consequently the choice of suitable material. In the development of the work were carried out: the qualification of the equipment of tests of filter media in the Laboratory of Environmental Control of the DEQ/UFSCar and the Laboratory of Test of Filters and Technology of Aerosols of DENERG of Politecnico di Torino in Italy according to the European Committee of Normalization (CEN/TC 195/WG 6), participation in the development of a standardized method of testing nanoparticles in conjunction with other laboratories worldwide, with filtration experiments for various media at the Laboratory of the Politecnico di Torino, under the supervision of the same working group as well. Several filtration efficiency tests were performed with eight different filter media, analyzing particles in the range of 10 to 500 nm. The collection efficiency of the filter media decreased from the first analyzed particle size until the MPPS, where it began to increase. Based on these studies performed with the virgin filters and due to the lack of studies on the performance of filtration media in the filtration of nanoparticles during their entire useful life, a modification was made in the test system of the Environmental Control Laboratory of DEQ/UFSCar, in accordance with ISO 16890: 3, and it was analyzed the filtration performance of two filter media from their initial pressure drop to the maximum pressure drop that could be reached. It has been observed that the higher filtration efficiency is achieved for an intermediate pressure drop. The collection efficiency obtained for the maximum pressure drop of the filter media was lower than the values obtained with the initial pressure drop.